Efficient computational modelling of smooth muscle orientation and function in the aorta - Rolf-Pissarczyk, Malte; Wollner, Maximilian P.; Pacheco, Douglas R.Q.; Holzapfel, Gerhard A. (Proceedings of the Royal Society A-Mathematical Physical and Engineering Sciences, 2021)
Understanding the mechanical effects of smooth muscle cell (SMC) contraction on the initiation and the propagation of cardiovascular diseases such as aortic dissection is critical. Framed by elastic lamellar sheets in the lamellar unit, there are SMCs in the media with a distinct radial tilt, which indicates their contribution to the radial strength. However, the mechanical effects of this type of anisotropy have not been fully discussed. Therefore, in this study, we propose a constitutive framework that models the passive and active mechanics of the aorta, taking into account the dispersed nature of the aortic constituents by applying the discrete fibre dispersion method. We suggest an isoparametric approach by evaluating various numerical integration methods and introducing a non-uniform discretization of the unit hemisphere to increase its computational efficiency. Finally, the constitutive parameters are fitted to layer-specific experimental data and initial computational results are briefly presented. The radial tilt of SMCs is also analysed, which has a noticeable influence on the mechanical behaviour of the aorta. In the absence of sufficient experimental data, the results indicate that the active contribution of SMCs has a remarkable impact on the mechanics of the healthy aorta.
Created from Fastlane, Scopus look-up
Keywords: constitutive modelling; contraction; discrete fibre dispersion model; fibre dispersion; smooth muscle cell